2020
DOI: 10.7759/cureus.11407
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-Biochemical Correlation in Birth Asphyxia and Its Effects on Outcome

Abstract: Background Birth asphyxia is a major cause of early neonatal death and leads to severe consequences such as epilepsy, cerebral palsy, and developmental delay. This study aims to determine the correlation between dyselectrolytemia and the degree of hypoxic-ischemic encephalopathy (HIE) and to find out major risk factors contributing to the severity of HIE and neonatal death. Methods In this prospective cohort study (n=150), term babies weighing ≥ 2.5 kg at birth, with the diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 20 publications
4
9
0
2
Order By: Relevance
“…Hypoglycaemia occurring in asphyxiated newborns is known to be closely associated with their long‐term neurological outcome, 22 and it is known that asphyxiated newborns represent a vulnerable population with risk of early hypoglycaemia 19 . Apart from hypoglycaemia, electrolyte disturbances such as hyponatremia or hypocalcaemia occurred, which is consistent with anomalies described in previous studies 23,24 25 it seems important to monitor the ionogram of this fragile population.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Hypoglycaemia occurring in asphyxiated newborns is known to be closely associated with their long‐term neurological outcome, 22 and it is known that asphyxiated newborns represent a vulnerable population with risk of early hypoglycaemia 19 . Apart from hypoglycaemia, electrolyte disturbances such as hyponatremia or hypocalcaemia occurred, which is consistent with anomalies described in previous studies 23,24 25 it seems important to monitor the ionogram of this fragile population.…”
Section: Discussionsupporting
confidence: 89%
“…19 Apart from hypoglycaemia, electrolyte disturbances such as hyponatremia or hypocalcaemia occurred, which is consistent with anomalies described in previous studies. 23,24 Knowing that electrolyte disturbances can increase the risk of seizures, 25 it seems important to monitor the ionogram of this fragile population. The frequency and severity of biological anomalies is known to be associated with the severity of HIE, 14 but organ dysfunction among asphyxiated newborns without moderate or severe HIE can occur, as described in our study.…”
Section: Discussionmentioning
confidence: 99%
“…We try to find out the single most investigation needed to yield the highest correlation with seizure, as the data regarding this is lacking in developing countries like India. Children with seizures must get a proper diagnosis at the earliest for better management and a good prognosis [ 5 ]. This prospective observational study was conducted to investigate the socio-demographic profile, clinical characteristics, hospital-based prevalence, and correlation of EEG and neuroimaging in children under 15 years with seizures in Odisha state.…”
Section: Introductionmentioning
confidence: 99%
“…MSAF and bloody amniotic fluid were found to be independent risk factors associated with birth asphyxia. 1,3,39,40 Bhatia et al indicated that free radicals were increased in the presence of MSAF and suggested that neonates with MSAF suffer from hypoxia regardless of the Apgar at birth. 41 Also, bloody amniotic fluid was associated with higher rates of placental abruption.…”
Section: Discussionmentioning
confidence: 99%